Managing public and nonprofit organizations stories of success and failure - Coe, Charles K. (Routledge, 2018)
Managing Public and Nonprofit Organizations approaches public management learning in a unique way, examining more than 100 high-profile and little-known administrative failure and success stories to explore how failures happen, how they can be prevented, and how to replicate successes in other jurisdictions. Organized to complement a standard public management or organizational behavior textbook structure, and to satisfy NASPAA accreditation requirements, this book explores both traditional public administration functions (performance management, financial management, human-resource management, procurement management, policymaking, capital management, and information-technology management) and organizational concepts (organizational structure and organizational culture). Unlike a traditional casebook, the accompanying stories do not stop in the middle to ask the readers what they would do; instead readers are asked to consider how the events illuminate what public management means and how to make it most effective. The stories ground and give meaning to the book’s review of principles and best practices.